Ethanol Extract of Pinus koraiensis Leaves Mitigates High Fructose-Induced Hepatic Triglyceride Accumulation and Hypertriglyceridemia - Min-Ho Lee; Sunyeong Park; Yinzhu Xu; Jung-Eun Kim; Hengmin Han; Jae-Hyeon Lee; Jean Kyung Paik; Hyo-Jeong Lee (Applied Sciences, 2022)
Pinus koraiensis is a valuable plant source of functional health foods and medicinal materials. Hypertriglyceridemia affects about 15–20% of adults and is related to stroke, metabolic syndromes, cardiovascular diseases, and diabetes mellitus. Dietary fructose, a risk factor for developing hypertriglyceridemia, significantly increases postprandial triglyceride (TG) levels and aggravates non-alcoholic fatty liver disease. In this study, we aimed to analyze the effect of ethanol extract from P. koraiensis needles (EPK) on fructose (Fr)-induced cell culture and animal models, respectively. Our team determined the bioactivity, such as anti-cancer, anti-obesity, anti-diabetic, and anti-hyperlipidemic functions, of P. koraiensis needle extract. The EPK markedly reduced TG levels in the liver and serum and enhanced TG excretion through feces in high-fructose-fed rats. Furthermore, the EPK inhibited de novo lipogenesis and its markers—carbohydrate response element-binding protein (ChREBP), sterol regulatory element-binding protein 1 (SREBP-1), fatty acid synthase (FAS), 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR), and tumor necrosis factor-alpha (TNF-α), a pro-inflammatory marker. Consistent with the results of the in vivo experiment, the EPK decreased SREBP-1, ChREBP, HMGCR, FAS, TNF-α, and iNOS expression levels, resulting in slower lipid accumulation and lower TG levels in Fr-induced HepG2 cells. These findings suggest that EPK mitigates hypertriglyceridemia and hepatic TG accumulation by inhibiting de novo lipogenic and pro-inflammatory factors.